“The Crimean war in the collective memory”: modern Western European historiography of the Crimean campaign of 1853-1856 - Marc de Bollivier (RUDN Journal of World History, 2019)
The article analyzes the modern Western historiography of the Crimean war of 1853-1856. The authors refer to problems and issues that prevail in the French and British studies of the events of 1853-1856. In the Western historiographical tradition based on researches of the XIX-XX centuries, still remain insuﬃciently explored aspects of the Crimean war, for example, the siege of Sevastopol, military operations in the Baltic and White seas, in the Paciﬁc ocean, in the Caucasus. Despite the obvious trend existing in modern European science, associated with the study of the Crimean campaign in the context of the ﬁrst pan-European war, the attention of historians of Western Europe is more focused on the study of the First world war. However, in recent years there has been a clear interest of French, English and Italian authors to the Black sea region, to the history of the Crimea and, as a consequence, to the Crimean campaign. Generalization of modern experience of historiography of the Crimean war allows to deﬁne prospects for further researches.